Anarchic dance - Aggiss, Liz; Cowie, Billy; Bramley, Ian, 1968- (Routledge, 2006)
This visual and textual record of the Divas Dance Theatre features extracts from Aggiss and Cowie's work and provides a comprehensive look at their collaborative partnership. The authors invite writers to examine their live performances through analysis, theory, discussion, and personal responses.